Kombinasi Metode SWARA dan Simple Additive Weighting (SAW) Pemilihan Tempat Kursus - I Wayan Sriyasa (PT. Tech Cart Press, 2023)
The combination of SWARA and SAW methods in course venue selection is a comprehensive approach to determining the best course place. The SWARA method is used to identify the relative weights of each criterion in the selection of course venues, with stepwise evaluation steps to produce accurate weight ratios. Furthermore, the SAW method is applied to give a weighted value to each alternative course place based on predetermined criteria. By combining the advantages of SWARA in criteria weighting analysis and SAW in alternative ranking, this approach provides more accurate and transparent results in choosing the course place that best suits the needs and preferences of users. The ranking results showed that rank 1 with a total value of 0.925 was obtained by Victoria, rank 2 with a total value of 0.9047 was obtained by Diamond, rank 3 with a total value of 0.8708 was obtained by Anisya, and the last rank with a total value of 0.8531 was obtained by Zalia.